Pengembangan buku ajar matematika berbasis higher order thinking skills - Indiyanti, Indiyanti; Asmarani , Dewi; Sutopo, Sutopo (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
The trend of new jobs in the future is based on digital technology, so that future needs are graduates from madrasahs who have analytical skills who can think critically. Making textbooks that are valid, practical and effective and in accordance with the needs of students is one way to cultivate a critical thinking attitude independently. The purpose of this research and development is to (1) develop a valid, practical and effective mathematics textbook. (2) knowing the effect of the use of HOTS-based mathematics textbooks on the crisis thinking ability of grade VII MTsN 7 Nganjuk students. The research and development model is the Borg ang Gall model. The data collection method uses validation sheets, observation sheets for the implementation of textbooks, student response questionnaires and tests to measure students' critical thinking skills. The subject is a student of class VII MTsN 7 Nganjuk. The data analysis technique uses a t-test using SPSS. . This research and development resulted in a product in the form of a valid textbook with the validation results of material experts 87%, media experts 85%. Practically based on the results of the student response questionnaire which is 89%. Effectively based on data from the post test value analysis using the t test, the learning outcomes using textbooks have a significant difference in the value of critical thinking ability compared to classes that do not use textbooks of 0.001 or < 0.05.